The communication by States of International Law to their direct stakeholders (2011)
From the beginning International law has been conceived as being between states. However, as a result of the progressive development of the law, new actors and new subjects have taken root. The individual is one of these and this has occurred in respect of different perspectives; under the criminal concept the individual may be held responsible before different ad hoc tribunals and the International Criminal Court. Also from the perspective of human rights. This article analyzes the means by which the state’s positions on matters of international law are conveyed to individuals, corporate entities and other actors.